Responding to Relative Energy Deficiency in Sport (REDs): a multidisciplinary care pathway for safe return to sport - Jenna M. Schulz; Jessica White; Carla Edwards; Selina Liu; Jane S. Thornton (Sports Psychiatry)
Abstract: Introduction: Relative energy deficiency in sport (REDs) is a syndrome of impaired physiological and/or psychological functioning caused by prolonged/severe low energy availability (LEA). The consequences associated with LEA may be challenging to manage and requires a team approach. As no guidelines currently exist on how to engage a multidisciplinary team, the objective of this study was to propose a team approach and clinical care pathway for clinicians involved in REDs care. Methods: Five expert clinicians from different perspectives [Physical Therapist (PT), Sport Medicine Physician (MD), Endocrinologist (Endo), Registered Dietitian (RD) and Sport Psychiatrist (Psych)] determined an optimal team approach to treatment, management and referral pathways for athletes presenting with REDs. Results: A clinical care pathway should follow initial risk stratification, diagnosis, and a team approach to management and return to sport (RTS). Each member of the clinical team plays different but important roles at each step, and relevant referrals should be initiated early and often. For instance, a referral to a PT may be initiated for concomitant injury management, and an RD for nutritional support. Furthermore, referral to an MD/Endo is warranted for diagnosis and ruling out other medical conditions, and referral to Psych for psychological factors that interfere with recovery. Forming and maintaining a clinical alliance between all practitioners is essential during the RTS phase to ensure consistency of messaging and approach. Conclusion: Each member of the clinical management team plays a unique yet integral role in guiding the athlete through the phases of REDs identification, management, and recovery. Engaging a comprehensive multidisciplinary team spanning physical and mental health as well as nutrition is recommended to optimize athlete health.